Negative plate and battery

By optimizing the number and spherical shape of silicon particles on the negative electrode surface, the battery's self-discharge and high-temperature storage issues are addressed, enhancing energy density and performance.

CN119627041APending Publication Date: 2025-03-14ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411820987.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing silicon-based particles in lithium-ion battery negative electrodes have irregular shapes with high corner areas, leading to SEI membrane thickening, increased particle size, and severe self-discharge issues, affecting battery energy density and high-temperature storage performance.

Method used

Adjusting the ratio of silicon particle number to average spherical shape within a 100μm×100μm area on the negative electrode surface to 1≤a≤50 and 0.66≤b≤1, where a is the particle number and b is the spherical shape, to reduce self-discharge and enhance high-temperature storage performance.

Benefits of technology

This approach effectively lowers self-discharge and improves the battery's high-temperature storage performance while maintaining high volumetric energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627041A_ABST
    Figure CN119627041A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative plate and a battery. The negative plate comprises a negative current collector and a negative active coating positioned on at least one side surface of the negative current collector, and the negative active coating comprises silicon-based particles; the number of the silicon-based particles in a 100 [mu] m * 100 [mu] m area on the surface of the negative electrode active coating is a, and a is greater than or equal to 1 and less than or The average sphericity of the silicon-based particles is b, and b is more than or equal to 0.66 and less than or equal to 1; a and b satisfy 1 < = a / b < = 67, the self-discharge degree of the battery can be reduced, and the high-temperature storage performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a battery. Background Art

[0002] With the rapid development of consumer electronics, electric vehicles, and energy storage power stations, using silicon-based materials with higher theoretical lithium storage capacity to replace traditional graphite materials as the negative electrode of the battery is an important way to further improve the energy density of lithium-ion batteries. However, the existing silicon-based particles are mainly irregular block particles with more edges and corners. Due to the large specific surface area at the edges and corners, during the cycle of lithium-ion batteries, the SEI film formed at the edges and corners becomes thicker, and the size of the silicon-based particles is increased, which makes it easy for the silicon-based particles on the surface of the negative electrode to protrude from the negative electrode active layer and pierce the diaphragm, resulting in more serious self-discharge and affecting the high-temperature storage performance of the battery. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art, and provide a negative electrode sheet and a battery comprising the negative electrode sheet. By adjusting the proportional relationship between the number of silicon-based particles and the average sphericity in the 100μm×100μm area on the surface of the negative electrode active coating, the self-discharge degree of the battery can be reduced and the high-temperature storage performance of the battery can be improved.

[0004] A first aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector, the negative electrode active coating comprising silicon-based particles; the number of the silicon-based particles within a 100 μm×100 μm area on the surface of the negative electrode active coating is a, 1≤a≤50; the average sphericity of the silicon-based particles is b, 0.66≤b≤1;

[0005] A second aspect of the present invention provides a battery, comprising the negative electrode sheet.

[0006] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0007] The negative electrode sheet provided by the present invention can reduce the degree of battery self-discharge and improve the high-temperature storage performance of the battery by adjusting the ratio between the number of silicon-based particles and the average sphericity in a 100 μm×100 μm area on the surface of the negative electrode active coating.

[0008] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 Shown is a SEM backscattering pattern image of the surface of a negative electrode sheet in an embodiment of the present invention.

[0010] Figure 2 Shown is a SEM backscattering pattern image of a cross-section of a negative electrode sheet in an embodiment of the present invention.

[0011] Figure numerals: 1. foil; 2. silicon-based particles; 3. carbon-based particles. DETAILED DESCRIPTION

[0012] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0013] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0014] In the present invention, the term "100 μm×100 μm region" refers to an arbitrary unit area of ​​100 μm×100 μm where the silicon-based particles are located on the surface of the negative electrode active coating.

[0015] A first aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector, the negative electrode active coating comprising silicon-based particles; the number of the silicon-based particles within a 100 μm×100 μm area on the surface of the negative electrode active coating is a, 1≤a≤50; the average sphericity of the silicon-based particles is b, 0.66≤b≤1;

[0016] a and b satisfy: 1≤a / b≤67.

[0017] Exemplarily, the value of a can be 1, 2, 4, 6, 8, 10, 15, 20, 25, 30, 35, 40, 42, 44, 46, 48, 50, or any point value in the range consisting of any two of the above point values.

[0018] Illustratively, the value of b can be 0.66, 0.67, 0.68, 0.69, 0.70, 0.75, 0.80, 0.85, 0.90, 0.92, 0.94, 0.96, 0.98, 1, or any point value in the range consisting of any two of the above point values.

[0019] Exemplarily, the value of a / b can be 1, 2, 3, 5, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 66, 67 or any point value in the range consisting of any two of the above point values.

[0020] In the present invention, when the average sphericity (b) of the silicon-based particles is adjusted to be within a suitable range (0.66≤b≤1), the number of silicon-based particles on the surface of the negative electrode active coating (a) can be adjusted to ensure that the negative electrode sheet has a high volume energy density while avoiding excessive volume expansion, thereby improving the safety of the battery. Silicon-based particles with higher sphericity can be more evenly distributed on the surface of the negative electrode active coating to form a more stable SEI film, which helps to reduce the volume change of the battery during the cycle.

[0021] Furthermore, when the number of silicon-based particles is increased in order to obtain a higher volume energy density of the negative electrode sheet, if the sphericity of the silicon-based particles is not increased accordingly, more silicon-based particles will cause too many angular structures to exist on the surface of the negative electrode active coating. These angular structures will cause the growth and thickening of the SEI film during the battery cycle, thereby causing the size of the silicon-based particles to increase, which may eventually cause the particles to protrude from the space of the negative electrode active coating and penetrate the diaphragm, causing serious self-discharge and deterioration of the high-temperature storage performance of the battery. On the contrary, if the number of silicon-based particles is small, although the angular structure on the surface of the negative electrode active coating can be reduced, the improvement of the volume energy density of the negative electrode sheet is not obvious. Therefore, the present invention controls the number of silicon-based particles on the surface of the negative electrode active coating (a) and the average sphericity of the silicon-based particles (b) to meet 1≤a / b≤67, which can effectively reduce the self-discharge coefficient of the battery while ensuring that the negative electrode sheet has a higher volume energy density, and improve the high-temperature storage performance of the battery.

[0022] In the present invention, when a satisfies: 1≤a≤50; b satisfies: 0.66≤b≤1, it is possible to avoid the situation when a<1, in which there are fewer silicon-based particles in the negative electrode active coating, resulting in a lower volume energy density of the battery; and to avoid the situation when b<0.66 and / or a>50, in which the sphericity of the silicon-based particles on the surface of the negative electrode active coating is low and / or the number of silicon-based particles is excessive, resulting in a higher degree of self-discharge of the battery and worsening the high temperature storage performance of the battery.

[0023] In some embodiments, a and b satisfy: 2≤a / b≤47; In one example, a and b satisfy: 2≤a / b≤23;

[0024] and / or, 2≤a≤40; in one example, a satisfies 2≤a≤20;

[0025] And / or, 0.85≤b≤1.

[0026] When the above range is further met, the self-discharge degree of the battery during the cycle can be better reduced, and the high-temperature storage performance of the battery can be further improved, while having a higher volume energy density.

[0027] Exemplarily, a test method for the number a of silicon-based particles within a 100 μm×100 μm area on the surface of the negative electrode active coating may include the following steps: first, dismantling the lithium-ion battery, taking out the negative electrode sheet, and soaking and rinsing it with dimethyl carbonate solvent to remove the lithium salt and electrolyte solvent on the negative electrode sheet, and observing it through a scanning electron microscope backscattering mode after drying. In the scanning electron microscope backscattering mode, the silicon-based particles present an overall brighter contrast, and the graphite particles are overall darker or only brighter at the edges (such as Figure 1 As shown in the figure, the imaging position is moved at a certain magnification (such as 500 times), and N non-overlapping 100μm×100μm areas are randomly selected. The number of overall brighter particles in each area is measured and the average value is finally taken, that is, the number of silicon-based particles in the 100μm×100μm area on the surface of the negative electrode active layer is obtained, where N≥10 and N is an integer. It should be noted that if the silicon-based particle is exactly at the boundary of the 100μm×100μm area, it will be regarded as a valid counting object if and only if the projected area of ​​the silicon-based particle in the 100μm×100μm area accounts for 50% or more.

[0028] Exemplarily, a test method for the average sphericity b of silicon-based particles may include the following steps: first, disassemble the lithium-ion battery, take out the negative electrode sheet, and soak and rinse it with dimethyl carbonate solvent to remove the lithium salt and electrolyte solvent on the negative electrode sheet. After drying, the cross-section of the negative electrode sheet is obtained by argon ion cutting. In the backscattering mode of the scanning electron microscope, the silicon-based particles present a brighter contrast, and the graphite particles are darker. Therefore, the image of each bright spot particle in the SEM backscattering mode photograph of the negative electrode sheet at a certain magnification (such as 2500 times) can be calculated by image processing software (such as Image ProPlus) to obtain the circumference and area of ​​each silicon-based particle, and the circumference equivalent radius r1 and area equivalent radius r2 of each particle are calculated respectively. Then, the sphericity of each particle is b=r2 / r1, and then the sphericity of each particle is weighted averaged by quantity, that is, the average sphericity b of the silicon-based particles in the cross-section of the negative electrode sheet is obtained.

[0029] In some embodiments, a cross-sectional image of the negative electrode sheet is obtained using a scanning electron microscope backscattering mode. Figure 2 As shown in the figure, the vertical strip with the highest brightness is foil 1, the particles that are brighter throughout are silicon-based particles 2, and the particles that are darker or have brighter edges are graphite particles 3.

[0030] In some embodiments, the Raman spectrum of the negative electrode active coating is at 470 cm -1-520cm -1 The first characteristic peak is at 1300cm -1 -1400cm -1 There is a second characteristic peak at 1520cm -1 -1620cm -1 It has a third characteristic peak; the ratio I of the intensity of the first characteristic peak to the intensity of the third characteristic peak is 0.001-0.2, for example, it can be 0.001, 0.003, 0.005, 0.008, 0.01, 0.03, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2 or any point value in the range composed of any two of the above point values. In one example, I is 0.01-0.15.

[0031] In the present invention, the first characteristic peak is a silicon peak. The more silicon-based particles there are on the surface of the negative electrode active coating, the stronger the intensity of the first characteristic peak. The second characteristic peak is a D peak, which indicates the defects and disorder of carbon on the surface of the negative electrode active coating. The third characteristic peak is a G peak, which indicates the lattice vibration and order of carbon on the surface of the negative electrode active coating. Since the order of carbon in graphite is much higher than that of carbon in silicon carbon, the intensity of the third characteristic peak can indicate the number of graphite particles on the surface of the negative electrode active coating. Therefore, the ratio I of the intensity of the first characteristic peak to the intensity of the third characteristic peak can indicate the proportion of silicon-based particles on the surface of the negative electrode active coating. The higher the I value, the greater the proportion of silicon-based particles. When the I value further meets the above range, the surface of the negative electrode active coating has a suitable proportion of silicon-based particles, which can make the negative electrode sheet have a higher volume energy density while improving the self-discharge of the battery, and improving the high temperature storage performance and rapid discharge capability of the battery. At the same time, when I<0.001 is avoided, the proportion of silicon-based particles on the surface of the negative electrode active coating is low, resulting in a low volume energy density of the battery, or the silicon-based particles are concentrated in the bottom layer of the active coating, so that the lithium-embedded expansion stress of the silicon-based particles is concentrated in the bottom layer, resulting in the breakage of the collector foil and causing irreversible loss of battery capacity; when I>0.2 is avoided, the proportion of silicon-based particles on the surface of the negative electrode active coating is too large, and it is easier to squeeze the diaphragm and produce self-discharge when the lithium-embedded volume expands. At the same time, the silicon-based particles are in more complete contact with the electrolyte, the side reactions are violent, and the battery's cycle and high-temperature storage performance are deteriorated.

[0032] In some embodiments, the compaction density of the negative electrode sheet is 1.25 g / cm 3 -1.9g / cm 3 , for example, 1.25 g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3, 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.85g / cm 3 , 1.9g / cm 3 Or any point value in the range of the above two point values; in one example, the compaction density of the negative electrode sheet is 1.4g / cm 3 -1.8g / cm 3 . Silicon-based particles with higher sphericity can disperse the rolling pressure more evenly during rolling, maintain the integrity of the particles, and thus enable the negative electrode sheet to achieve a higher compaction density. When the compaction density of the negative electrode sheet meets the above range, it can further improve the volume energy density of the lithium-ion battery, so that the battery has both a higher volume energy density and better rapid discharge capability. At the same time, it can also improve the problem of increased specific surface area of ​​silicon-based particles and increased side reactions due to the breakage of silicon-based particles during battery cycling. When the compaction density of the negative electrode sheet is <1.25g / cm 3 When the negative electrode sheet has a low surface density, the volume energy density of the lithium-ion battery is low; when the compaction density of the negative electrode sheet is greater than 1.9 g / cm 3 When the negative electrode is charged, the pore volume retained inside the negative electrode is small, which can easily cause poor contact between some active material particles and the electrolyte, affecting the battery's rapid discharge capability.

[0033] Exemplarily, the method for determining the compaction density of the negative electrode sheet may include the following steps: disassembling the lithium-ion battery and taking out the negative electrode sheet, soaking and rinsing it with dimethyl carbonate, and drying it, using a micrometer to measure the thickness of the foil at multiple points in the empty foil area where no active material is coated on both sides, calculating the average thickness of the foil, and then measuring the thickness at multiple positions in the double-sided coating area, thereby calculating the thickness of the negative electrode active layer. Then, a slicer is used to cut several small discs with a diameter of 12 mm from the empty foil area and the double-sided coating area, and the average mass of the empty foil small disc and the double-sided coating small disc is weighed to obtain the mass of the single-sided negative electrode active layer on the small disc, and then the compaction density of the negative electrode active layer on the negative electrode sheet is calculated based on the area of ​​the small disc and the thickness of the negative electrode active layer.

[0034] In some embodiments, the mass content of the silicon-based particles in the negative electrode active coating is 2%-95%, for example, it can be 2%, 4%, 6%, 8%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 91%, 92%, 93%, 94%, 95% or any point value in the range composed of two points above; in one example, the mass content of the silicon-based particles in the negative electrode active coating is 5%-90%. Since the silicon-based particles have a higher specific capacity, when the mass content of the silicon-based particles in the negative electrode active coating meets the above range, the volume energy density of the battery can be improved. If the content of silicon-based particles is <2%, the silicon content in the silicon-based particles is less, and the volume energy density of the battery is lower; if the content of silicon-based particles is >95%, the content of carbon-based materials in the negative electrode sheet is less, resulting in low conductivity and poor rapid discharge capability of lithium-ion batteries.

[0035] Exemplarily, the method for determining the mass content of silicon-based particles in the negative electrode active coating may include the following steps: disassembling the lithium-ion battery and taking out the negative electrode sheet, soaking and rinsing with dimethyl carbonate, and drying, selecting at least 5 silicon-based particles in the SEM backscattering mode, obtaining the silicon content percentage of each silicon-based particle by the EDS point scanning mode, and calculating the average silicon content ratio in the silicon-based particles. Then the dried negative electrode sheet is treated at 400°C for 2h (such as a tube furnace, nitrogen or argon atmosphere), and the negative electrode active material layer can be peeled off from the current collector to collect the negative electrode active material. In the silicon content test, a thermogravimetric analyzer (such as a TGA 550 thermogravimetric analyzer) is used, the sample amount for the test is 5mg-15mg, and the temperature is increased from room temperature to 900°C at a heating rate of 10°C / min in an air or oxygen atmosphere, and kept at 900°C for 40min, so that the non-silicon components in the active layer of the negative electrode material are volatilized while the silicon can be fully oxidized to silicon dioxide. The weight percentage at the end of the entire test process is the ash content of the negative electrode active layer; the ash value is divided by the molar mass of silicon dioxide and then multiplied by the molar mass of silicon to obtain the percentage of silicon in the negative electrode active layer. The mass content of silicon-based particles in the negative electrode active coating can be calculated from the percentage of silicon and the average silicon content of silicon-based particles.

[0036] In some embodiments, the silicon-based particles include at least one of elemental silicon, silicon carbon, silicon oxygen and silicon alloys; in one example, the silicon-based particles include silicon carbon, and the structure of the silicon carbon is a porous carbon-deposited silicon material (the silicon material includes at least one of elemental silicon, silicon carbon compounds, lithium silicon compounds and silicon oxygen compounds), specifically, the silicon carbon includes a skeleton, the skeleton includes a porous carbon skeleton body and a silicon material, the porous carbon skeleton body has pores, and the silicon material fills at least part of the pores of the porous carbon skeleton body.

[0037] In some embodiments, the negative electrode active coating further includes carbon-based particles; the ratio D1 / D2 of the average particle size D1 of the carbon-based particles to the average particle size D2 of the silicon-based particles is 1-5, and the value of D1 / D2 can be, for example, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or any point value in the range consisting of any two of the above point values; in one example, D1 / D2 is 1.1-2.5.

[0038] When the average particle size D2 of silicon-based particles and the average particle size D1 of carbon-based particles further satisfy the above-mentioned proportional relationship, during the rolling process, the carbon-based particles can quickly adapt to pressure due to their good elasticity. Under the appropriate particle size ratio, a closer contact interface can be formed between silicon-based particles and carbon-based particles, reducing the pores and defects of the negative electrode active coating; the negative electrode active coating formed is also more uniform and smooth, which also helps to form a more uniform and stable SEI film, improve the interface stability, thereby further reducing the self-discharge of the battery, improving the high-temperature storage performance of the battery, and making the battery have a higher volume energy density. At the same time, on the one hand, it avoids the situation when D1 / D2<1, the particle size of the silicon-based particles is too large or the particle size of the carbon-based particles is too small. The larger silicon-based particles are easy to protrude from the range of the negative electrode active layer and damage the diaphragm, affecting the self-discharge and high-temperature storage performance of the battery. The smaller carbon-based particles are more likely to have side reactions with the electrolyte during the charge and discharge process due to their larger specific surface area, resulting in poor high-temperature storage performance of the battery and accelerated cycle retention rate attenuation; on the other hand, it also avoids the situation when D1 / D2>5, the particle size of the silicon-based particles is too small or the particle size of the carbon-based particles is too large. The specific surface area of ​​the small silicon-based particles is also large, and they are also easy to have side reactions with the electrolyte, affecting the high-temperature storage and cycle performance of the battery. The larger the particle size of the carbon-based particles, the longer the lithium ion diffusion path at the core, which makes the battery's rapid discharge capability poor.

[0039] In some embodiments, the average particle size D1 of the carbon-based particles is 8 μm-20 μm, and D1 can be, for example, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 19 μm, 20 μm, or any point value in the range of any two of the above point values. In one example, D1 is 10 μm-18 μm;

[0040] And / or, the average particle size D2 of the silicon-based particles is 4μm-20μm, and D2 can be, for example, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 15μm, 18μm, 20μm or any point value in the range composed of any two of the above point values. In one example, D2 is 6μm-11μm.

[0041] When the average particle size D1 of the carbon-based particles and / or the average particle size D2 of the silicon-based particles further meet the above range, the volume energy density of the battery can be further improved and the battery can have a lower self-discharge coefficient and better high-temperature storage performance.

[0042] In the present invention, "average particle size" refers to the average value of geometric diameters of a number of particles, which can be obtained by measuring a number of particles, for example, the average value of geometric diameters can be obtained by measuring a dozen or dozens of particles.

[0043] Exemplarily, a method for determining the average particle size of silicon-based particles and the average particle size of carbon-based particles in a negative electrode active coating may include the following steps: first, disassemble the lithium-ion battery, take out the negative electrode sheet, and soak and rinse it with dimethyl carbonate solvent to remove the lithium salt and electrolyte solvent on the negative electrode sheet, and observe it through a scanning electron microscope backscattering mode after drying. In the scanning electron microscope backscattering mode, randomly measure the maximum diameters of 50 silicon-based particles (particles with brighter contrast) and the maximum diameters of 50 carbon-based particles (particles with darker contrast), and calculate the arithmetic mean of the measured maximum diameters of the 50 silicon-based particles and the maximum diameters of the 50 carbon-based particles, respectively. The results obtained are the average particle size of the silicon-based particles and the average particle size of the carbon-based particles.

[0044] In some other embodiments, the Dv50 of the carbon-based particles is 8 μm-20 μm, for example, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 19 μm, 20 μm or any point value in the range of any two of the above points;

[0045] And / or, the Dv50 of the silicon-based particles is 4μm-20μm, for example, it can be 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 15μm, 18μm, 20μm or any point value in the range consisting of any two of the above point values.

[0046] When the Dv50 of the carbon-based particles and / or the Dv50 of the silicon-based particles further meet the above range, it is also possible to increase the volume energy density of the battery, improve the self-discharge system of the battery, and enhance the high-temperature storage performance of the battery.

[0047] For example, in the negative electrode active coating, the Dv50 of the silicon-based particles and the Dv50 of the carbon-based particles can be tested using a laser particle size analyzer, for example, a Malvern Mastersizer 3000 laser particle size analyzer. In the present invention, "Dv50" is the particle size corresponding to the cumulative volume distribution of 50% after the particles are arranged from small to large.

[0048] In some embodiments, the type of the carbon-based particles includes, but is not limited to, at least one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon.

[0049] In some embodiments, the negative electrode active coating further includes a conductive agent, which includes but is not limited to at least one of acetylene black, conductive carbon black, Ketjen black, conductive graphite, carbon nanotubes, conductive carbon fibers, and graphene. Further adding a conductive agent can further improve the conductivity of the battery, thereby improving the rapid discharge capability of the battery.

[0050] A second aspect of the present invention provides a battery, comprising any one of the above-mentioned negative electrode sheets.

[0051] In some embodiments, the battery further comprises a diaphragm, and the thickness c of the diaphragm is 3 μm-9 μm, for example, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm or any point value in the range composed of the above two point values; in one example, the thickness c of the diaphragm is 4 μm-8 μm. Since the negative electrode active coating has a silicon-carbon material with good sphericity, the thickness of the diaphragm can be controlled within the above range, which can effectively reduce the thickness of the battery and make the lithium-ion battery have a higher volume energy density. At the same time, when the thickness of the diaphragm is <3 μm, the strength of the diaphragm is too low, and it is easy to be punctured by silicon-based particles, which deteriorates the self-discharge and high-temperature storage performance of the battery, and a too thin diaphragm is easy to cause the interface with the negative electrode active coating to be not firmly bonded, and the pole piece is prone to powdering.

[0052] Exemplarily, the method for measuring the thickness c of the diaphragm may include the following steps: after disassembling the lithium-ion battery, taking out the diaphragm, soaking and rinsing it with a dimethyl carbonate solution, and after drying it, measuring the thickness of 10 positions of the diaphragm vertically with a micrometer, and then averaging the results to obtain the thickness c of the diaphragm.

[0053] In the present invention, the types of separators include but are not limited to at least one of woven membranes, nonwoven membranes (nonwoven fabrics), microporous membranes, composite membranes, separator paper, rolled membranes, polyethylene microporous membranes, and polypropylene microporous membranes.

[0054] In some embodiments, the Raman spectrum of the negative electrode active coating is at 470 cm -1 -520cm -1 The first characteristic peak is at 1300cm -1 -1400cm -1 There is a second characteristic peak at 1520cm -1 -1620cm -1It has a third characteristic peak; the ratio of the intensity of the first characteristic peak to the intensity of the third characteristic peak I and c satisfy: 0.002≤I / c≤0.04, and the value of I / c can be, for example, 0.002, 0.003, 0.004, 0.005, 0.008, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04 or any point value in the range composed of the above two point values. In one example, I and c satisfy: 0.005≤I / c≤0.03. The higher the I value, the higher the proportion of silicon-based particles in the negative electrode active coating close to the diaphragm side. The higher the proportion of silicon-based particles, to a certain extent, can reflect that the number of silicon-based particles is greater, so the risk of piercing the diaphragm increases, so it is necessary to increase the thickness c of the diaphragm to prevent the diaphragm from being pierced by the edges or protrusions of the silicon-based particles, affecting the battery performance. When the ratio I of the intensity of the first characteristic peak to the intensity of the third characteristic peak and the thickness c of the diaphragm further meet the above range, the battery can take into account high volume energy density, further improve the high temperature storage performance of the battery, and reduce the degree of self-discharge of the battery.

[0055] In some embodiments, the battery also includes an electrolyte; the electrolyte includes fluoroethylene carbonate; the fluoroethylene carbonate in the electrolyte can form a thinner and dense SEI film on the surface of silicon-based particles, which can alleviate the size growth of silicon-based particles during the cycle process to a certain extent, and further improve the battery self-discharge and high-temperature storage performance deterioration problems caused by silicon-based particles.

[0056] In some embodiments, the mass content of fluoroethylene carbonate (FEC) in the electrolyte is 0.1%-5%, for example, it can be 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any point value in the range composed of any two of the above points. Further, when the mass content of fluoroethylene carbonate in the electrolyte meets the above range, it can avoid that when the content of fluoroethylene carbonate is less than 0.1%, the improvement effect is not obvious, and when the content of FEC is greater than 5%, the viscosity of the electrolyte is too large, the conductivity of the electrolyte is reduced, and the rapid discharge capability of the battery is affected.

[0057] Exemplarily, the method for determining the content of fluoroethylene carbonate in an electrolyte may include the following steps: preparing a dichloromethane standard solution of fluoroethylene carbonate with concentrations of 0.5 μg / mL, 1 μg / mL, 2.5 μg / mL, 5 μg / mL, 20 μg / mL, and 50 μg / mL, respectively, and using a gas chromatography-mass spectrometry (GC-MS, equipment parameters: column flow rate 1 mL / min, injection temperature 250°C, split ratio 20:1, DB-1701 gas chromatography column, injection volume 1 μL, ion source temperature 260°C, ionization energy 70 eV, GC interface temperature 270°C, ionization mode EI, collection mode SIR mode) instrument, taking the mass-to-charge ratio m / z=62 as the quantitative ion chromatographic peak, and plotting a standard curve using the area of ​​the peak versus the concentration of the standard solution. The lithium-ion battery was then disassembled, the electrolyte was collected and a certain amount of electrolyte was drawn with a pipette, and then a 1 μg / mL mixed solution was prepared with dichloromethane as a diluent. The sample was injected five times continuously, and the mass content of FEC in the electrolyte was calculated based on the standard curve and the peak area at the mass-to-charge ratio m / z=62.

[0058] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0059] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0060] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0061] The following examples are provided to illustrate the batteries of the present invention.

[0062] Example 1

[0063] Prepare the battery as follows:

[0064] 1) Preparation of negative electrode

[0065] Silicon-based particles (silicon carbon, porous carbon deposited silicon material structure; sphericity 0.9, average particle size D29μm), artificial graphite (average particle size D1 12μm), polyacrylic acid, sodium carboxymethyl cellulose, styrene-butadiene rubber, SuperP, and carbon nanotubes were mixed in a ratio of 10:82:3:1.6:1.6:1.7:0.1, deionized water was added, and a negative electrode slurry was obtained under the action of a vacuum mixer. The negative electrode slurry was evenly coated on the surface of both sides of the negative electrode current collector with a thickness of , and the surface density of the negative electrode slurry coated on the surface of the negative electrode current collector was 6mg / cm 2The negative electrode current collector coated with the negative electrode slurry was transferred to an oven at 80°C for drying for 12 h, and then roller pressed (the compaction density was controlled to be 1.78 g / cm 3 ), cut into pieces to obtain the negative electrode sheet.

[0066] 2) Preparation of positive electrode

[0067] Lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), acetylene black and carbon nanotubes (CNTs) are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone is added, and stirred under the action of a vacuum mixer until a uniform positive electrode slurry is mixed. The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 9 μm. The coated aluminum foil is baked in an oven, then transferred to an oven at 120°C and dried for 8 hours, and then rolled and cut to obtain the desired positive electrode sheet. The size of the positive electrode sheet is smaller than that of the negative electrode sheet, and the reversible capacity per unit area of ​​the positive electrode sheet is 4% lower than that of the negative electrode sheet.

[0068] 3) Diaphragm

[0069] A polyethylene diaphragm with a thickness of 5 μm was selected.

[0070] 4) Preparation of lithium-ion batteries

[0071] The positive electrode sheet of step 2), the separator of step 3), and the negative electrode sheet of step 1) are stacked in order, ensuring that the separator is between the positive and negative electrode sheets to play an isolating role, and then the bare battery cell is obtained by winding. The bare battery cell is placed in an aluminum-plastic film shell, and the electrolyte (1 mol / L LiPF6+EC / DMC (1:1; by volume)+1wt.% FEC) is injected into the dried bare battery cell, and the required battery is obtained through vacuum packaging, standing, formation, shaping, sorting and other processes.

[0072] Performance parameter test:

[0073] i) Energy density test

[0074] The lithium ion batteries prepared in the examples and comparative examples were subjected to energy density tests, and the specific test methods are as follows:

[0075] The battery was charged at a constant current of 0.2C to 4.5V, then charged at a constant voltage of 4.5V with a cut-off current of 0.02C. After standing for 10 minutes, it was discharged at a constant current of 0.2C to 3.0V, and stood for 10 minutes. The first-cycle discharge capacity and first-cycle discharge energy of the battery were recorded. The battery was then charged at a constant current of 0.2C with a cut-off condition that the charging capacity reached half of the first-cycle discharge capacity. After the cut-off, the battery was removed and the thickness, length and width of the battery were measured. The energy density of the battery = first-cycle discharge energy / (length × width × thickness).

[0076] ii) Self-discharge test

[0077] The lithium ion batteries prepared in the examples and comparative examples were subjected to self-discharge tests, and the specific test methods are as follows:

[0078] The battery was charged at a constant current density of 0.2C to 4.5V, and then charged at a constant voltage of 4.5V with a cut-off current of 0.02C. After standing for 10 minutes, the open circuit voltage V1 of the battery was recorded. Then, the battery was kept standing for 24 hours, and the open circuit voltage V2 of the battery was recorded after the standing was completed. The self-discharge degree of the battery is k (mV / h) = (V1-V2) / 24 (in mV / h).

[0079] iii) Storage performance test

[0080] The lithium ion batteries prepared in the examples and comparative examples were tested for storage performance, and the specific testing method is as follows:

[0081] The battery was charged to 4.5V at a current density of 0.2C, then charged at a constant voltage of 4.5V with a cutoff current of 0.02C. After standing for 10 minutes, it was discharged to 3.0V at a current density of 0.2C and stood for 10 minutes, and the first-cycle discharge capacity of the battery was recorded; the battery was then charged at a current density of 0.2C with a constant current, and the cutoff condition was that the charging capacity reached half of the first-cycle discharge capacity. After the cutoff, the battery was removed and the thickness of the battery was measured, which was recorded as the thickness before storage; the battery was then charged to 4.5V at a current density of 0.2C with a constant current, then charged at a constant voltage of 4.5V with a cutoff current of 0.02C, and then placed in a 60°C blast oven for 35 days. At the end of the placement, its thickness was tested and recorded as the thickness after storage. The thickness expansion rate of the battery after storage at 60°C for 35 days = (thickness after storage - thickness before storage) / thickness before storage.

[0082] iv) Cyclic performance test

[0083] The lithium ion batteries prepared in the examples and comparative examples were subjected to cycle tests, and the specific test methods are as follows:

[0084] The battery is charged to 4.5V at a current density of 2C, then charged at a constant voltage of 4.5V with a cut-off current of 0.05C, then left to stand for 10 minutes, and then discharged to 3.0V at a current density of 1.5C, then left to stand for 10 minutes, and the discharge capacity of the battery at this time is recorded as the initial capacity; repeat the above charge and discharge process until the 500th cycle of constant voltage charging process is completed and left to stand for 10 minutes, then discharged to 3.0V at a current density of 1.5C, left to stand for 10 minutes, and the discharge capacity of the battery at this time is recorded as the capacity after the cycle. Then the cycle capacity retention rate = (capacity after the cycle / initial capacity) × 100%.

[0085] v) Rate discharge capability test

[0086] The lithium ion batteries prepared in the examples and comparative examples were subjected to rate discharge capacity tests, and the specific test methods are as follows:

[0087] The battery was charged to 4.5V at a current density of 0.2C, then charged at a constant voltage of 4.5V with a cut-off current of 0.02C. After standing for 10 minutes, it was discharged to 3.0V at current densities of 0.2C and 1C respectively. The ratio of the capacity released at 1C to the capacity released at 0.2C is the rate discharge capability of the battery.

[0088] The Example 1-2 group and the Comparative Example 1-3 are carried out with reference to the Example 1-1, and the main differences are shown in Table 1. Among them, the Example 1 group is the number (a) of silicon-based particles in the 100μm×100μm area on the surface of the negative electrode active coating layer. The Example 2 group is the average sphericity (b) of the silicon-based particles. The Comparative Example 1 is that the values ​​of a, b and a / b do not meet the protection range. The Comparative Example 2 is that the number (a) of silicon-based particles is too large. The Comparative Example 3 is that the average sphericity (b) is too small.

[0089] Table 1

[0090]

[0091]

[0092] As can be seen from Table 1, the present invention controls the number of silicon-based particles on the surface of the negative electrode active coating (a) and the average sphericity of the silicon-based particles (b) to satisfy 1≤a / b≤67, thereby ensuring that the negative electrode sheet has a high volume energy density while effectively reducing the self-discharge coefficient of the battery and improving the high-temperature storage performance of the battery.

[0093] The Example 3 group was carried out with reference to the Example 1-1, and the main differences are shown in Table 2. Among them, the Example 3 group is the change in the compaction density of the negative electrode sheet.

[0094] Table 2

[0095]

[0096]

[0097] As can be seen from Table 2, the present invention, by adding silicon-based particles with higher sphericity to the negative electrode active coating, can enable the negative electrode sheet to achieve a higher compaction density during roller pressing, further improving the volume energy density of the lithium-ion battery, so that the battery has both a higher volume energy density and better rapid discharge capability.

[0098] The Example 4 group was carried out with reference to the Example 1-1, and the main differences are shown in Table 3. Among them, the Example 4 group is that the mass content of the silicon-based particles is changed based on the total mass of the negative electrode active coating.

[0099] Table 3

[0100]

[0101] As can be seen from Table 3, the present invention can improve the volume energy density of the battery by controlling the mass content of the silicon-based material of the negative electrode sheet, while avoiding the situation where the content of silicon-based particles is too high and the content of the binder and conductive agent in the negative electrode active coating is too low, which affects the capacity retention rate and rate performance of the battery.

[0102] The examples 5-6 were carried out in accordance with the examples 1-1, and the main differences are shown in Table 4. In the example 5, the average particle size (D1) of the carbon-based particles was changed. In the example 6, the average particle size (D2) of the silicon-based particles was changed.

[0103] Table 4

[0104]

[0105]

[0106] As can be seen from Table 4, the present invention can further improve the volume energy density of the battery and enable the battery to have a lower self-discharge coefficient and better high-temperature storage performance by controlling the ratio range of D1, D2 and D1 / D2. At the same time, on the one hand, it can avoid the silicon-based particles or carbon-based particles having too small a particle size, which will increase the side reactions of the battery due to the large specific surface area, resulting in poor high-temperature storage performance and capacity retention of the battery; on the other hand, it can avoid the silicon-based particles or carbon-based particles having too large a particle size, resulting in poor battery rate performance; if the silicon-based particles have too large a particle size, the k value and high-temperature storage performance of the battery will be further deteriorated.

[0107] Example 7 was carried out in accordance with Example 1-1, and the main differences are shown in Table 5. In Example 7, the mass content of fluoroethylene carbonate (FEC) in the electrolyte was changed.

[0108] Table 5

[0109]

[0110] As can be seen from Table 5, the present invention adds FEC to the electrolyte and notifies the mass content of FEC in the electrolyte, which can alleviate the size growth of silicon-based particles during the cycle process to a certain extent and further improve the battery self-discharge and high-temperature storage performance deterioration problems caused by silicon-based particles.

[0111] The examples 8-9 were carried out in accordance with the examples 1-1, and the main differences are shown in Table 6. In the example 8, the amount of silicon-based particles added to the negative electrode active coating was changed, so that the ratio I of the intensity of the first characteristic peak to the intensity of the third characteristic peak in the Raman spectrum of the negative electrode active coating was changed. In the example 9, the thickness (c) of the battery separator was changed.

[0112] Table 6

[0113]

[0114] It can be seen from Table 6 that, by controlling the ratio range of the ratio I of the intensity of the first characteristic peak to the intensity of the third characteristic peak and the thickness c of the diaphragm, the battery can take into account high volume energy density, further improve the high temperature storage performance of the battery, and reduce the self-discharge of the battery. At the same time, when the thickness of the diaphragm is too thin, the strength of the diaphragm is low, and it is more easily punctured by silicon-based particles, which deteriorates the self-discharge and storage performance of the battery. In addition, the use of an overly thin diaphragm can easily lead to a loose interface bonding with the negative electrode coating, which can easily cause the electrode to powder.

[0115] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector, wherein the negative electrode active coating comprises silicon-based particles; the number of the silicon-based particles within a 100 μm×100 μm area on the surface of the negative electrode active coating is a, 1≤a≤50; the average sphericity of the silicon-based particles is b, 0.66≤b≤1; a and b satisfy: 1≤a / b≤67.

2. The negative electrode sheet according to claim 1, wherein: 2≤a / b≤47; preferably 2≤a / b≤23; and / or, 2≤a≤40; preferably 2≤a≤20; And / or, 0.85≤b≤1.

3. The negative electrode sheet according to claim 1 or 2, wherein: The Raman spectrum of the negative electrode active coating is at 470 cm -1 -520cm -1 The first characteristic peak is at 1300cm -1 -1400cm -1 There is a second characteristic peak at 1520cm -1 -1620cm -1 having a third characteristic peak; a ratio I of the intensity of the first characteristic peak to the intensity of the third characteristic peak is 0.001-0.2; Preferably, I is 0.01-0.

15.

4. The negative electrode sheet according to claim 1 or 2, wherein: The compaction density of the negative electrode sheet is 1.25 g / cm 3 -1.9g / cm 3 ; Preferably, the compaction density of the negative electrode sheet is 1.4 g / cm 3 -1.8g / cm 3 .

5. The negative electrode sheet according to claim 1 or 2, wherein: The mass content of the silicon-based particles in the negative electrode active coating is 2%-95% based on the total mass of the negative electrode active coating; Preferably, based on the total mass of the negative electrode active coating, the mass content of the silicon-based particles in the negative electrode active coating is 5%-90%; and / or, the silicon-based particles include at least one of elemental silicon, silicon-carbon, silicon-oxygen and silicon alloy; Preferably, the silicon-based particles comprise silicon carbon.

6. The negative electrode sheet according to claim 1 or 2, wherein: The negative electrode active coating further comprises carbon-based particles; the ratio D1 / D2 of the average particle size D1 of the carbon-based particles to the average particle size D2 of the silicon-based particles is 1-5; Preferably, D1 / D2 is 1.1-2.

5.

7. The negative electrode sheet according to claim 6, wherein: The average particle size D1 of the carbon-based particles is 8 μm-20 μm; And / or, the average particle size D2 of the silicon-based particles is 4 μm-20 μm.

8. A battery, characterized in that: The battery comprises the negative electrode sheet according to any one of claims 1 to 7.

9. The battery according to claim 8, wherein The battery further comprises a separator, wherein the thickness c of the separator is 3 μm-9 μm; Preferably, the Raman spectrum of the negative electrode active coating is at 470 cm -1 -520cm -1 The first characteristic peak is at 1300cm -1 -1400cm -1 There is a second characteristic peak at 1520cm -1 -1620cm -1 It has a third characteristic peak; the ratio I of the intensity of the first characteristic peak to the intensity of the third characteristic peak and c satisfies: 0.002≤I / c≤0.04; more preferably, 0.005≤I / c≤0.

03.

10. The battery according to claim 8, wherein The battery also includes an electrolyte; the electrolyte includes fluoroethylene carbonate; Preferably, the mass content of fluoroethylene carbonate in the electrolyte is 0.1%-5%.